Analisis Wacana Kritis Van Dijk terhadap Pesan Moral dalam Web Series Bidaah - Fajar Maulidil Ali; Jasafat; Hanifah Nurdin (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This study analyzes the moral messages presented in the web series Bidaah using Teun A. Van Dijk’s Critical Discourse Analysis model. The research problem arises from the growing presence of distorted religious representations in digital media, which increasingly shape public perceptions of religious authority. The study aims to reveal how meaning is constructed through textual structures, the social cognition of the film’s creators, and the broader social context surrounding the production of Bidaah. The research method involves direct observation of the series, systematic documentation of its narrative and visual elements, and a review of relevant literature. The findings show that Bidaah conveys strong moral messages about the misuse of religion, the exercise of power, and the importance of critically pursuing truth. At the textual level, the film highlights the tension between dogma and common sense through the depiction of character conflicts. At the level of social cognition, it reflects the creators’ intention to encourage viewers to think critically about the legitimacy of religious authority. At the contextual level, the series mirrors ongoing issues of religious manipulation in contemporary society. The study concludes that Bidaah functions not only as entertainment but also as an educational medium that promotes a rational and humanistic understanding of religion. The contribution of this research lies in mapping the structure of moral messages in digital media content and demonstrating the usefulness of Van Dijk’s discourse analysis model for examining religious representation in popular culture.